Performance of plant-produced RBDs as SARS-CoV-2 diagnostic reagents: a tale of two plant platforms - Santoni, Mattia; Gutierrez-Valdes, Noemi; Pivotto, Denise; Zanichelli, Elena; Rosa, Anthony; Sobrino-Mengual, Guillermo; Balieu, Juliette; Lerouge, Patrice; Bardor, Muriel; Cecchetto, Riccardo; Compri, Monica; Mazzariol, Annarita; et al. (Frontiers in Plant Science, 2024)
The COVID-19 pandemic has underscored the need for rapid and cost-effective diagnostic tools.Serological tests, particularly those measuring antibodies targeting the receptor-binding domain (RBD) of the virus, play a pivotal role in tracking infection dynamics and vaccine effectiveness. In this study, we aimed to develop a simple enzyme-linked immunosorbent assay (ELISA) for measuring RBD-specific antibodies, comparing two plant-based platforms for diagnostic reagent production.We chose to retain RBD in the endoplasmic reticulum (ER) to prevent potential immunoreactivity issues associated with plant-specific glycans. We produced ER-retained RBD in two plant systems: a stable transformation of BY-2 plant cell culture (BY2-RBD) and transient transformation in Nicotiana benthamiana using the MagnICON system (NB-RBD). Both systems demonstrated their suitability, with varying yields and production timelines.The plant-made proteins revealed unexpected differences in N-glycan profiles, with BY2-RBD displaying oligo-mannosidic N-glycans and NB-RBD exhibiting a more complex glycan profile. This difference may be attributed to higher recombinant protein synthesis in the N. benthamiana system, potentially overloading the ER retention signal, causing some protein to traffic to the Golgi apparatus.When used as diagnostic reagents in ELISA, BY2-RBD outperformed NB-RBD in terms of sensitivity, specificity, and correlation with a commercial kit. This discrepancy may be due to the distinct glycan profiles, as complex glycans on NB-RBD may impact immunoreactivity.In conclusion, our study highlights the potential of plant-based systems for rapid diagnostic reagent production during emergencies. However, transient expression systems, while offering shorter timelines, introduce higher heterogeneity in recombinant protein forms, necessitating careful consideration in serological test development.* reported accumulation levels are converted when possible to mg/kg FW to facilitate comparison